Peran Majlis Taklim Fathul Huda dalam Meningkatkan Pemahaman Agama Islam - Fatkhurrokhman Fatkhurrokhman; Srifariyati Srifariyati (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2022)
The purpose of this study was to determine the role of Majlis taklim in increasing the understanding of Islam in the Datar Warungpring village community. This study uses a qualitative approach (field research). The primary data sources of this study consisted of caregivers, Teachers and students of Majlis Taklim Fathul Huda, while the secondary data sources were documents, The data collection technique is through observation, interviews and documentation. The results of this study are (1) the role of the administrator and teachers of Majlis Taklim Fathul Huda in Datar village, namely motivating, training and monitoring students to be active in learning, practicing and broadcasting Islam in the community. (2) The activities of the Fathul Huda in Datar village can be grouped into three types, namely the Qur'an recitation which is held after the Asr prayer and after the Maghrib prayer, the Bandungan recitation of the Salaf books using the classical system. Skills education among its activities is Qiro'ah (The art of reading the Qur'an), Simtudduror and speech skills. (3) The understanding of Islam by the students of Majlis Taklim Fathul Huda is good.